TRADITIONAL AND INNOVATIVE APPROACHES TO STUDENTS OF UKRAINIAN LANGUAGE BY COLLEGE STUDENTS - Шашенко, В.; Сахно, З. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
Nowadays, the ongoing changes in the Ukrainian education are aimed towards the development of an intelligent person, capable to social adaptation and representation by means of language. It is emphasized by the National Doctrine of the Development of Education in Ukraine, the State Standard of Basic and Complete Education and, of course, by the school programs. Updating the content of the course “Ukrainian language”, increasing attention to the study of the state language in higher educational establishments, practical orientation in the language teaching as a compulsory discipline, as well as the definition of tasks for the formation of professional competences of future specialists by means of speech, contribute to the improvement of forms, methods, learning technologies. The analysis of traditional and innovative approaches to the study of the Ukrainian language is the subject of the study of many domestic and foreign pedagogues, methodologists, psychologists (Holub N.V., Lyubashenko O.V., Pionova R.S., Symonenko T.V., Surmin Yu. P., etc). The article deals with the traditional and innovative approaches to the study of Ukrainian language. Special teaching techniques of the process of Ukrainian language studying for schoolchildren have been submitted as well. In this paper we prove the principles of specificity, openness and clarity. The lessons are always focused and are aimed for achieving of some definite goals. The main thing at the lesson is the organization of students’ work as well as the ability to interest and attract them to perform various types of activities, so we are constantly in search for the new methods and techniques of training and education. Creating conditions for the development and self-realization of each individual as a citizen of Ukraine as well as the formation of generations capable of learning throughout life, will gradually facilitate the quality of the training and educational process simultaneously with overall functioning of the higher educational establishment